2021
DOI: 10.3390/su13137243
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Economic Impacts of Climate Change on Net Crop Income in the Ethiopian Nile Basin: A Ricardian Fixed Effect Approach

Abstract: Climate change affects crop production by distorting the indestructible productive power of the land. The objective of this study is to examine the economic impacts of climate change on net crop income in Nile Basin Ethiopia using a Ricardian fixed effect approach employing the International Food Policy Research Institute (IFPRI) household survey data for Ethiopia in 2015 and 2016. The survey samples were obtained through a three-stage stratified sampling technique from the five regions (Amhara, Tigray, Benish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…However, [27] found that climate change will probably have only relatively small effects on the average yields of maize, wheat, and sorghum in Ethiopia in 2035 and even in 2055. [28] illustrate that Ethiopian Nile Basins are negatively affected by climate change at varying levels. The higher increase in growing season temperatures combined with high inter-annual and intraseasonal variability of rainfall adversely affect crop production [20].…”
Section: Introductionmentioning
confidence: 97%
“…However, [27] found that climate change will probably have only relatively small effects on the average yields of maize, wheat, and sorghum in Ethiopia in 2035 and even in 2055. [28] illustrate that Ethiopian Nile Basins are negatively affected by climate change at varying levels. The higher increase in growing season temperatures combined with high inter-annual and intraseasonal variability of rainfall adversely affect crop production [20].…”
Section: Introductionmentioning
confidence: 97%
“…In India, agriculture and allied activities contributed about 18.3 percent of total gross value added (GVA) in 2022-23 (Press Information Bureau, 2023. The climate change and global warming has impacted the different crops differently (Baylie and Fogarassy, 2021).Wheat is one of the most consumed food crops in India as well as globally. Wheat ensures food security in India specifically the northern part of the country.…”
mentioning
confidence: 99%
“…In India, agriculture and allied activities contributed about 18.3 percent of total gross value added (GVA) in 2022-23 (Press Information Bureau, 2023. The climate change and global warming has impacted the different crops differently (Baylie and Fogarassy, 2021).…”
mentioning
confidence: 99%